Pentingnya Pembentukan Aturan Pemindahan Narapidana Asing Antar Negara Sebagai Upaya Perlindungan Terhadap HAM - Laode, Nadila Magfira (Universitas Muhammadiyah Metro, 2025)
The transfer of prisoners between countries is an increasingly common form of international cooperation. This step is considered effective in protecting human rights, as it allows prisoners to undergo a rehabilitation process in their home country. Every Indonesian citizen and foreign citizen residing in the territory of Indonesia is given recognition of rights as a legal subject along with legal protection from the State. Human rights law emphasizes that there are 3 (three) duties of the state, namely the obligation to respect, the obligation to protect, and the obligation to fullfil the rights of citizens. In the realm of constitutional law, the state's legal obligations are regulated in Article 28 I paragraph (4) of the 1945 Constitution of the Republic of Indonesia, as well as Article 8 and Article 71 of Law Number 39 of 1999 concerning Human Rights, which further contains the state's duty to promote and protect. The Indonesian government has received many requests to transfer prisoners abroad. However, until now Indonesia has not carried out such transfers due to the absence of regulations or legal frameworks governing the procedures for transferring prisoners in the national legal system. This research uses a normative method by examining laws and regulations related to the subject of research to understand the existing problems.